'A real African woman!' Multipositionality and its effects in the field. (June 2021) - Dodworth, Kathy
Critical ethnographic inquiry demands flux in the researcher's positionality in a double sense. The first is in its attempts to interweave the micro with macro structures of power and domination, demanding a multi-sited aspect, in sensibility as much as locality. The second, following the reflexive turn, is to dismantle the violence of epistemological realism through turning one's analytical tools onto one's Self. This turn spotlights the fluidity and ambiguity of one's identity, disruptive of and disrupted by relations in the 'field'. Whilst critical inquiry often aspires to emancipate the Self as well as Others, the toll of multipositionality in the field should not be taken lightly. Critical inquiry and its arsenal, of which ethnography forms an integral part, demands a dynamism that can indeed liberate but also incarcerate, without due attention. An honest and reflexive conversation about the emotional and psychological demands of such research is long overdue.